Pension Systems (Un)sustainability and Fiscal Constraints: A Comparative Analysis - Burkhard Heer; Vito Polito; Mike Wickens (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using an overlapping generations model, two new indicators of public pension system sustainability are proposed: the pension space, which measures the capacity to pay for pension expenditures out of labour taxation, and the pension space exhaustion probability reflecting demographic uncertainties. These measures reveal that the pension spaces of advanced economies are strikingly different. Most nations have little scope to further finance pensions out of labour income taxation over the next thirty years. There is no one-size-fits-all solution. Risk-equivalent pension reforms enhance welfare in the long run, particularly for rapidly ageing nations, but also entail non-negligible transitional costs.
Keywords: E62; H55; H20; 330; ageing; fiscal space; public pension sustainability; overlapping generations model